Study on the performance of natural fiber reinforced concrete of different strength with DIP technique and T- Test Analysis - Ramalingam GEETHA; Ramalingam VIJAYALAKSHMI (Journal of Materials and Engineering Structures, 2023)
This work focuses on the effect of natural plant fiber as reinforcement on the strength properties of concrete of different grade strength (M30-M50). Fibers of different length were added to the concrete mix at the rate 3% of the binder content. Three different lengths of fibers (10-30 mm) at fixed volume fraction were added to M30, M40 and M50 grades of concrete. The fresh and mechanical property of twelve different fiber reinforced concrete mixes was investigated.  The effect of fibers on the pre cracking, post cracking behaviour of the concrete specimen was investigated using digital image processing technique and video measuring system images.  Using the developed linear regression plot, empirical equations were formulated to establish relation between the compressive strength and other mechanical properties of concrete. From the study it can be concluded that the caryota fiber with rich cellulose content contributes to arrest the cracks at the initial stage of loading and prevents major crack plane in the post peak region. Fibers mainly contribute to increase the tensile property of concrete. The effect of fibers is more prominent in M30 mix concrete when compared to M40 and M50 concrete mixes.